ANALISIS HUKUM PERKAWINAN SEJENIS: PERSPEKTIF HAK ASASI MANUSIA - Muhammad Yanri Chairyatna (Fakultas Hukum Universitas Udayana, 2023)
The aim of the research is to find out the human rights perspective regarding same-sex marriage and compare it with Law No. 1/1974 concerning marriage. The research method used is the normative juridical method, research that examines legal principles or norms. The existence of LGBT groups from a human rights perspective. Human Rights as referred to in Law No.39/1999 are a set of privileges bestowed upon us as creatures of God Almighty which must be respected, upheld and safeguarded by the legal system, government and every individual for their own interests. protection of our honor and dignity. According to the provisions of Law No. 1/1974, marriage is often carried out through relations between a man and a woman, especially with the aim of producing children and creating the desired household. If a relationship has the potential to transmit sexually transmitted diseases, then this violates human rights; Therefore, same-sex relationships are prohibited by the Marriage Law and cannot be legally recognized as a valid marriage.